THE PREPARATION AND SOLUBILITY OF LORATADINE-FUMARIC ACID BINARY MIXTURE - Alatas, Fikri; Aprilliana, Morisa; Gozali, Dolih (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Loratadine (LOR) is a biopharmaceutics classification system Class II drug that has low solubility and high permeability, so its absorption rate is determined by the dissolution rate. The aim of this study was to prepare an LOR-fumaric acid (LOR-FUM) binary mixture and to investigate its influence on the solubility and dissolution rate of LOR. Methods: LOR-FUM binary mixture was prepared by the wet grinding method in an equimolar ratio by the addition of two drops of methanol. Characterization of LOR-FUM binary mixture was conducted by the construction of the phase solubility, powder X-ray diffractometry, Fourier transforms infrared spectroscopy, and polarizing microscopy methods. Solubility test was performed in water at room temperature, whereas the in vitro dissolution test was performed in the pH 1.2, 4.5, and 6.8 buffer solutions. Results: The phase solubility curve of LOR in FUM solution is similar to type B . The powder X-ray diffraction results show the crystallinity of LOR was changed become more amorphous indicating the salt formation. Fourier transforms infrared spectroscopy (FTIR) spectra of LOR-FUM binary mixture showed the vibration peaks of an imine group on the pyridine ring of LOR and carbonyl group on the FUM are not detected. On the other hand, the polarizing microscope images showed the crystal habit of LOR-FUM binary mixture after recrystallized from methanol contrast to crystal habit of its pure components. The solubility in water of LOR-FUM binary mixture was higher than pure LOR. Amount of LOR released from LOR-FUM binary mixture in pH 4.5 and 6.8 buffer solutions was faster than from pure LOR. Conclusion: A binary mixture of LOR and FUM may improve the solubility and dissolution rate of LOR. Keywords: Loratadine, Fumaric acid, Binary mixture, Solubility, Dissolution rate.